The Endogenous Relative Price of Investment - Joel Wagner (Bank of Canada, 2015)
This paper takes a full-information model-based approach to evaluate the link between investment-specific technology and the inverse of the relative price of investment. The two-sector model presented includes monopolistic competition where firms can vary the markup charged on their product depending on the number of firms competing. With these changes to the standard two-sector model, both total factor productivity as well as a series of non-technological shocks can impact the high-frequency volatility of the relative price of investment. Utilizing a Bayesian estimation approach to match the model to the data, we find that investment-specific technology can explain at most half of the growth rate of the relative price of investment. Last of all, we compare the benchmark model results with endogenous movement in the relative price of investment to a model where all movement in the relative price of investment is derived exogenously. This is done by allowing technologies across sectors to move together over time. Comparison of these two methods finds that the exogenous approach is incapable of capturing changes in the relative price of investment as found in the data. This paper adds to the growing list of research, like that of Fisher (2009) and Basu et al. (2013), that suggests that the qualityadjusted relative price of investment may be a poor indicator of investment-specific technology.
Keywords: E32; L11; L16; 330; Business fluctuations and cycles